Inventory Management Techniques and the Performance of Supermarkets in Embu County. - Kibugi, Grace Wanja (University of Embu, 2019)
In today's highly competitive business environment, organizations are striving to achieve effectiveness, cost efficiencies and economies of scale. Most of these organizations hold inventory so as to meet their customers' needs. However, managing these inventories in order to achieve their objectives has posed a great challenge to the firms. Many firms have not yet established how much to invest in inventories and the right inventory levels to hold so as satisfy customers. Organizations have therefore turned to using inventory management techniques to overcome such challenges. Inventory management techniques are tools used by firms to attain supply chain performance .This study sought to establish the relationship between inventory management techniques and the performance of supermarkets. The study was guided by two objectives: to determine the effects of inventory management techniques on supermarket performance in Embu County and to determine extent of inventory management techniques applications in supermarkets . .. The study employed a descriptive research design and targeted all the supermarkets in Embu County. Data was collected from 6 operational supermarkets in Embu. Data was gathered using structured questionnaires and analyzed using both descriptive and inferential statistics, with the help of Statistical Package for Social Sciences (SPSS) The findings of the study revealed that inventory management techniques affected the performance of the supermarkets and that there was a positive linear relationship between inventory management techniques and the performance of the supermarkets. The linear regression model used revealed that 63 .4% of the supermarkets' performance could be explained by inventory management (r 2 =0.634). The extent of inventory management was found to be high among the supermarkets, with an overall mean score of 3.89, and the performance was also found to be high with an overall mean score of 4.13 both variables being rated on a scale of I to 5. The study recommended that supermarkets should make full use of their inventory management techniques so as to improve customer service delivery levels and reduce operational costs. The study also suggested that further research should be conducted on the effect of inventory management techniques on inventory investment and profits and also on challenges faced by the supermarkets in implementing their inventory management systems and how to overcome them.